An unusual new species of the genus Paulianellus (Coleoptera: Scarabaeidae: Aphodiinae) from Yunnan, China - Minkina, Łukasz; Král, David (Zootaxa, 2018)
The genus Paulianellus was erected by Balthasar (1938) as a subgenus of the genus Aphodius Hellwig, 1798 for a single species, Aphodius maderi Balthasar, 1938 from Sichuan.